Elevated serum carboxy-terminal telopeptide of type I collagen predicts clinical outcome in patients with acute coronary syndrome who underwent percutaneous coronary intervention. (25th November 2020) - Aono, T; Watanabe, T; Toshima, T; Takahashi, T; Otaki, Y; Wanezaki, M; Kutsuzawa, D; Kato, S; Tamura, H; Nishiyama, S; Takahashi, H; Arimoto, T; et al.
Abstract: Introduction: Serum carboxy-terminal telopeptide of type I collagen (I-CTP) is a collagen degradation product of type I collagen in the extracellular matrix of the heart, blood vessels, and bone. The serum levels of I-CTP were reportedly a predictive marker for cardiac remodeling after acute myocardial infarction. However, it remains unclear whether I-CTP can predict poor clinical outcome in patient with acute coronary syndrome (ACS). Purpose: The aim of this study was to investigate the association between serum levels of I-CTP and clinical outcome in patients with ACS. Methods: Serum levels of I-CTP were measured in 200 patients with ACS who underwent percutaneous coronary intervention (PCI). All patients were prospectively followed during the median follow-up period of 1312 days with the end point of major adverse cardiovascular events (MACE). We divided the patients into tertiles according to serum I-CTP level: low I-CTP group (≤4.4 ng/ml, n=72), middle I-CTP group (4.4–6.4 ng/ml, n=65), and high I-CTP group (≥6.5 ng/ml, n=63). Results: There were 44 MACE, including 24 all-cause death and 9 rehospitalization due to heart failure. I-CTP was significantly higher in patients with MACE than those without (4.90 [interquartile range (IQR): 3.80–6.38] ng/ml vs. 6.65 [IQR: 5.00–10.08] ng/ml, p<0.001). Kaplan-Meier analysis demonstrated that patients in the highest tertile of I-CTP had the greatest risk of MACE. In a univariate analysis, age, Albumin, estimated glomerular filtration rate (eGFR), low-density lipoprotein cholesterol (LDL-C), brain natriuretic peptide (BNP), high-sensitivity C-reactive protein (hsCRP) and I-CTP were significant predictors of MACE. A multivariate Cox proportional hazard analysis showed that the high I-CTP group had a higher risk for MACE (Hazard ratio [HR] 2.6, p=0.049) compared with the low I-CTP group after adjusting for confounding factors. Conclusions: I-CTP was significantly associated with MACE, suggesting that I-CTP could be a reliable marker for clinical outcome in patients with ACS who underwent PCI. Funding Acknowledgement: Type of funding source: None